Novel murine models for studying Cache Valley virus pathogenesis and in utero transmission. Issue 1 (1st January 2021) - López, Krisangel; Wilson, Sarah N.; Coutermash-Ott, Sheryl; Tanelus, Manette; Stone, William B.; Porier, Danielle L.; Auguste, Dawn I.; Muller, John A.; Allicock, Orchid M.; Paulson, Sally L.; Erasmus, Jesse H.; Auguste, Albert J.
ABSTRACT: Cache Valley virus (CVV) is a prevalent emerging pathogen of significant importance to agricultural and human health in North America. Emergence in livestock can result in substantial agroeconomic losses resulting from the severe embryonic lethality associated with infection during pregnancy. Although CVV pathogenesis has been well described in ruminants, small animal models are still unavailable, which limits our ability to study its pathogenesis and perform preclinical testing of therapeutics. Herein, we explored CVV pathogenesis, tissue tropism, and disease outcomes in a variety of murine models, including immune -competent and -compromised animals. Our results show that development of CVV disease in mice is dependent on innate immune responses, and type I interferon signalling is essential for preventing infection in mice. IFN-αβR -/- mice infected with CVV present with significant disease and lethal infections, with minimal differences in age-dependent pathogenesis, suggesting this model is appropriate for pathogenesis-related, and short- and long-term therapeutic studies. We also developed a novel CVV in utero transmission model that showed high rates of transmission, spontaneous abortions, and congenital malformations during infection. CVV infection presents a wide tissue tropism, with significant amplification in liver, spleen, and placenta tissues. Immune-competent mice are generally resistant to infection, and only show disease in an age dependent manner. Given the high seropositivity rates in regions of North America, and the continuing geographic expansion of competent mosquito vectors, the risk of epidemic and epizootic emergence of CVV is high, and interventions are needed for this important pathogen.